Reabilitação protética implantossuportada em região anterior maxilar com utilização de gengiva artificial cerâmica: relato de caso - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Arsufi, Guilherme Saavedra [UNESP]; Medeiros, Rodrigo Antonio de [UNESP]; Paulini, Marcela Borghi [UNESP]; Villa, Luiz Marcelo Ribeiro [UNESP] (My University, 2012)
The osseointegrated implants created a progress in oral rehabilitation. But this rehabilitation may be complicated by anatomical conditions, mainly in maxillary anterior region, where a higher aesthetic is required. The aim of study was to report one case which the use of angled abutments were necessary to allow the correct positioning of the prosthesis and also the prosthetic reconstruction with gingival-colored ceramic to provide best aesthetic result for patient. The aesthetic and functional results provided greater patient satisfaction with her smile. The correct planning is essential to provide to patient the best aesthetic and functional results, being necessary the use of abutments and gingival-colored ceramic to reach better results. Uniterms: dental implantacion, esthetics, mouth rehabilitation.

Os implantes osseointegrados trouxeram um grande avanço na área de reabilitação oral. Porém essa reabilitação pode ser dificultada devido às condições anatômicas, principalmente em regiões maxilares anteriores, onde se necessita de uma maior estética. O objetivo do estudo é relatar um caso onde foi necessária a utilização de intermediários angulados com a finalidade de permitir o correto posicionamento da prótese, e reconstrução protética com gengiva artificial cerâmica para proporcionar o melhor resultado estético ao paciente. O resultado estético e funcional forneceu ao paciente uma maior satisfação com seu sorriso. Um correto planejamento é essencial para que possa fornecer ao paciente o melhor resultado estético e funcional, sendo necessária a utilização de alguns componentes para se chegar ao melhor resultado, como a utilização de intermediários e gengivas artificiais.
Implant-supported prosthetic rehabilitation in maxillary anterior region with gingival-colored ceramic: case report
Keywords: Dental implantation; Esthetics; Mouth rehabilitation; Implante dentário; Estética; Reabilitação bucal